Implementation of Internal Audit Control System to Support the Accuracy of CV AFCO Fresh Financial Reports - Aprillia Zubaidah Azzahra; Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
This study aims to analyze the impact of changes in audit methods on the accuracy of stock opname reports at CV Afco Fresh. Stock opname is a crucial activity in inventory management that ensures the accuracy between physical stock and recorded inventory data in financial reports. Initially, the audit method involved scheduling audits in advance, which created opportunities for fraud among outlets. This method was then changed to simultaneous audits across all outlets to close data manipulation loopholes. This qualitative study uses a case study approach involving in-depth interviews, observations, and document reviews related to audit proced ures and stock opname reporting. The findings indicate that the change to simultaneous audits significantly improved the integrity and accuracy of stock opname reports, thereby enhancing the reliability of the company’s financial statements. This change also reduced errors and fraud risks, increasing stakeholder confidence in inventory data. The study recommends strengthening supervision, utilizing supporting technologies, and enhancing training as further steps to maintain audit quality and report accuracy.